85.2k views
5 votes
Solve the system by elimination. {2x+y=13x−y=−4 A. (3, 7) B. (2, 6) C. (4, 8) D. no solution

User Trisek
by
5.6k points

2 Answers

4 votes

Answer:

Explanation:

2x+y=13

x - y =-4 lets add both equations

3x=13-4

x=9/3 , x=3

3-y=-4, y=7

choice A

User Redexp
by
4.6k points
2 votes

Answer:

A

Explanation:

Given the 2 equations

2x + y = 13 → (1)

x - y = - 4 → (2)

Add the 2 equations term by term to eliminate the y- term, that is

3x = 9 ( divide both sides by 3 )

x = 3

Substitute x = 3 into either of the 2 equations and solve for y

Substituting into (1)

2(3) + y = 13

6 + y = 13 ( subtract 6 from both sides )

y = 7

solution is (3, 7 ) → A

User Kvdb
by
5.3k points